Fragmentation of XML Documents - Ma, Hui; Schewe, Klaus-Dieter (Journal of Information and Data Management, 2010)
The world-wide web (WWW) is often considered to be the world’s largest database and the eXtensible Markup Language (XML) is then considered to provide its datamodel. Adopting this view we have to deal with a distributed database. This raises the question, how to obtain a suitable distribution design for XML documents. In this paper horizontal and vertical fragmentation techniques are generalised from the relational datamodel to XML. Furthermore, splitting will be introduced as a third kind of fragmentation. Then it is shown how relational techniques for de ning reasonable fragments can be applied to the case of XML.